Homicide clearances during pre- and post-U.S. crime drop eras: the role of structural predictors and demographic shifts, 1976–2015 - Mancik, Ashley M. (Journal of crime and justice, 2019)
Increased attention to the U.S. crime drop has heightened awareness of the rise and fall in homicide rates over time, and the role structural and demographic characteristics have played in these shifts. Less is known about temporal patterns in homicide clearances and whether those same factors are equally relevant to clearance trends. Using a sample of large U.S. cities, this study offers a systematic investigation into the structural and demographic factors that contribute to within-city changes in homicide clearances from 1976 to 2015, while also controlling for other possible explanations, including changes in the nature of homicide and police workload. We find that structural and demographic shifts play significant roles in homicide clearance trends, even after controlling for both workload and case composition characteristics. Key differences emerge, however, when examining homicide clearances prior to and then after the 1990s U.S. crime drop.